The Effect of Social Media Marketing and Word of Mouth on Marketing Promotion with Brand Image as a Mediating Variable at Flamboyan MSMEs in Gorontalo - Darman Darman; Aulia Abdul Rahman; Irfan Akadji (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the influence of Social Media Marketing and Word of Mouth on Marketing Promotion with Brand Image as a mediating variable in Flamboyan Gorontalo MSMEs. This study is motivated by the importance of utilizing social media and word of mouth communication in increasing the effectiveness of MSME marketing promotion amidst increasingly competitive business competition. The research method used is a quantitative approach with a survey technique. Data were obtained by distributing questionnaires to consumers who have purchased Flamboyan Gorontalo MSME products. The sampling technique used was accidental sampling. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through the SmartPLS application. The results of the study indicate that Brand Image has a positive and significant effect on Marketing Promotion. Word of Mouth has a positive and significant effect on Brand Image. Conversely, Social Media Marketing has no significant effect on Brand Image or Marketing Promotion. In addition, Word of Mouth also has no significant effect on Marketing Promotion. The results of the indirect effect test indicate that Brand Image is unable to mediate the effect of Social Media Marketing on Marketing Promotion or the effect of Word of Mouth on Marketing Promotion. The research findings indicate that the success of marketing promotions in the Flamboyan Gorontalo MSME is more determined by the strength of its brand image than by social media marketing activities and direct word-of-mouth communication. This research contributes to the development of digital marketing and brand management literature, and provides input for MSMEs in designing marketing strategies that focus on strengthening brand image to increase the effectiveness of marketing promotions and business competitiveness.